Substantiation of Resource Territories Development: Complex "Meso-Level" Problem - Kryukov, Valeriy Anatolievich; Sevastyanova, Anastasiya Yegorovna; Tokarev, Anatoliy Nikolaevich; Shmat, Vladimir Vitalyevich (Economy of Regions, 2015)
The paper presents an approach to the analysis and evaluation of integrated investment projects, which consist of infrastructure facilities and industrial clusters, allocated in poorly developed areas rich with natural resources. It shows the feasibility of a public-private partnership during the construction of infrastructure facilities in order to minimize the risks and maximize the benefits. The conceptual framework of developed approach is associated with the ideas and principles of the «impact investing» («creating shared values») and inclusive economic development. These are increasingly used in the world, especially to accelerate the socio-economic development of the backward countries and territories. The article describes an international experience and justifies the relevance of the application of these concepts to the Russian context. We revealed methodical problems associated with the applying of traditional methods to evaluate economic effects of the project investment in conditions of high uncertainty. It is necessary to use models and methods (real options analysis, fuzzy cognitive models), which allow directly to take into account uncertainty and project risks. The novelty of the article consists in methodical tools for evaluating the socio-economic efficiency of the complex projects for infrastructure development and resources development. The elaborated approach has been applied for substantiation of the road construction project in the Berezovsky district of Khanty-Mansi Autonomous Okrug. It is shown that there are opportunities to generate a complex of institutional, organizational and financial conditions, under which the implementation of the project will be attractive for investors and for the state and will bring socio-economic benefits to the territory. The proposed approach and tools can be used in the socio-economic strategic planning under the justification of infrastructure projects in the new development areas of resource rich regions.